2021
DOI: 10.1007/s10072-021-05075-8
|View full text |Cite
|
Sign up to set email alerts
|

Facemask headache: a new nosographic entity among healthcare providers in COVID-19 era

Abstract: Background SARS-CoV-2 is a novel infectious agent causing coronavirus disease 2019, which has been declared as pandemic in March 2020. Personal protective equipment has been mandatory for healthcare workers in order to contain the outbreak of pandemic disease. Mild neurological disturbances such as headache have been related to the extensive utilization of facemask. This study aims to examine headache variations related to the intensive utilization of facemask among a cohort of healthcare professionals in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 33 publications
4
36
0
1
Order By: Relevance
“…New PPE-associated headaches were associated with the presence of pre-existing primary headaches and combined PPE usage > 4 h/day [ 29 ]. Additionally, a study consisting of 383 Italian healthcare providers found that 44 (26.5 %) developed de novo facemask-associated headache [ 30 ]. In our study, 31.8 % were involved in frontline work, and 12.5 % were healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…New PPE-associated headaches were associated with the presence of pre-existing primary headaches and combined PPE usage > 4 h/day [ 29 ]. Additionally, a study consisting of 383 Italian healthcare providers found that 44 (26.5 %) developed de novo facemask-associated headache [ 30 ]. In our study, 31.8 % were involved in frontline work, and 12.5 % were healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PPE-associated headaches amongst healthcare workers in the context of the COVID-19 pandemic ranges from 26.5%–90.7% [ 24 , 25 ••, 26 – 32 , 33 •, 34 •, 35 •, 36 •]. In comparison, a study amongst healthcare providers using the N95 face mask during the 2003 severe acute respiratory distress syndrome (SARS) epidemic in Singapore observed that new-onset face mask–associated headaches occurred with an incidence of 37.3% [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Since the start of COVID-19 in December 2019, there have been a total of 6 published studies specifically conducted to understand PPE-associated headache amongst healthcare workers (see Table 1 ) [ 25 ••, 33 •, 34 •, 35 •, 36 •, 38 •]. Based on these studies, several factors have been found to confer a greater likelihood of developing de novo PPE-associated headaches.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations